Synthesis, structures and biomolecular interactions of new silver(i) 5, 5-diethylbarbiturate complexes of monophosphines targeting Gram-positive bacteria and breast cancer cells. Issue 25 (13th June 2017) - Yilmaz, Veysel T.; Icsel, Ceyda; Batur, Jenaidullah; Aydinlik, Seyma; Cengiz, Murat; Buyukgungor, Orhan
Abstract : New silver(i ) 5, 5-diethylbarbiturate complexes exhibit very high antimicrobial activity against Gram-positive bacteria and kill MCF-7 cells, damaging mitochondria and DNA. Abstract : A series of new silver(i ) 5, 5-diethylbarbiturate (barb) complexes with the formulas [Ag2 (μ-barb)2 (PPh3 )2 ] (1 ), [Ag(barb)(PPh2 Cy)] (2 ), [Ag(barb)(PPhCy2 )] (3 ) and [Ag(barb)(PCy3 )] (4 ) (PPh3 = triphenylphosphine, PPh2 Cy = diphenylcyclohexylphosphine, PPhCy2 = dicyclohexylphenylphosphine and PCy3 = tricyclohexylphosphine) were synthesized and fully characterized by elemental analysis, IR, NMR, ESI-MS and X-ray crystallography. All the complexes display a significant affinity towards DNA with a groove binding mode and also strongly bind to BSA via hydrophobic interactions. Lipophilicity increases from1 to4 with an increasing number of Cy groups in the phosphine ligands. Screening of the in vitro antimicrobial activity of1–4 against the strains of Gram-negative ( S . typhimurium ATCC 14028, E . coli ATCC 25922 and O157:H7) and Gram-positive ( L . garvieae 40456, S . aureus ATCC 25923, and ATCC 33591) bacteria demonstrated that all the complexes exhibit very high activity and specific selectivity against the Gram-positive bacteria, compared to AgNO3 and silver sulfadiazine. Furthermore, the growth inhibitory effects of1–4 on four human cancer cell lines (MCF-7, PC-3, A549 and HT-29) showed that4 has a potent cytotoxic activity against MCF-7 cells, significantly higher than cisplatin and carboplatin. The effects of the complexes on the inhibition of the cells are closely related to their lipophilicity as well as DNA/protein binding. The induction of apoptosis of MCF-7 cells treated with4 was probed through Hoechst 33342 staining, Annexin V positivity and caspase 3/7 activity. In addition, increased ROS levels in the presence of4 are most likely responsible for damage to both mitochondria and genomic DNA.